Proteostasis and Diseases of the Motor Unit - Rinaldi, Carlo; Mäger, Imre; Wood, Matthew J. (Frontiers in Molecular Neuroscience, 2016)
The accumulation in neurons of aberrant protein species, the pathological hallmark of many neurodegenerative diseases, results from a global impairment of key cellular processes governing protein synthesis/degradation and repair mechanisms, also known as the proteostasis network. The growing number of connections between dysfunction of this intricate network of pathways and diseases of the motor unit, where both motor neurons and muscle are primarily affected, has provided momentum to investigate the muscle- and motor neuron-specific response to physiological and pathological stressors and to explore the therapeutic opportunities that manipulation of this process may offer. Furthermore, these diseases offer an unparalleled opportunity to deepen our understanding of the molecular mechanisms behind the intertissue communication and transfer of signals of proteostasis. The most compelling aspect of these investigations is their immediate potential for therapeutic impact: targeting muscle to stem degeneration of the motor unit would represent a dramatic paradigm therapeutic shift for treating these devastating diseases. Here we will review the current state of the art of the research on the alterations of the proteostasis network in diseases of the motor unit and its potential to result in effective treatments for these devastating neuromuscular disorders.